THE STUDY OF SLANG WORDS IN MEGAN THEE STALLION™S LYRICS - Lumban Gaol, Josua Erithelen; Gutom, Feriyanti Elina (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
Slang words are a form of linguistic variant that people adopt as a new vocabulary to use in everyday situations. When the slang words are analyzed into social functions, the detail of the language becomes clear. This research aimed to discover the social functions of slang words in Megan Thee Stallion™s lyrics in an album Good News through theory Zhou & Fan (2013). This research aimed to (a) investigate the social functions of slang words that are used, (b) elucidate how the social functions of slang words are used and (c) explain the reason of using the slang words. The qualitative descriptive method was used for this research. This research obtained 35 slang words as data used in Megan Thee Stallion. The part of emotive feeling is the highest percentage than the other parts which is more frequently expressing her feeling use slang words than other parts with 24 data reached 54%, pursuit of self-identity with 19 data reached 40%, and achieving politeness with 2 data reached 6%. Therefore, the usage of slang words is not used randomly, but it has the social functions of slang words which are pursuit of self-identity, emotive feeling of the slang users, and achieving politeness.